(untitled) (Journal of Science & Technology, 2020)
Software quality is a critical factor in ensuring the success of software projects. Numerous software quality models have been proposed and developed to assess and improve the quality of software products. This article presents a comprehensive review of various software quality models, examining their key concepts, methodologies, strengths, and limitations. The objective is to provide a valuable resource for researchers, practitioners, and decision-makers in the software development industry to make informed decisions about selecting and implementing appropriate software quality models.